Improving the Public Sector Development Programme Allocations in the Clientelistic Environment of Balochistan: A Political Economy Analysis (The Pakistan Development Review, 2025)
Successive governments in Balochistan have failed to streamline the Public Sector Development Programme (PSDP). This study discusses how political clientelism influences the process of PSDP by diverting scarce resources to create incentives for powerful political actors to keep the public dependent and poor. An analysis of the disbursement of PSDP in the 10 districts in the last ten years clearly shows that some districts with more population and area receive fewer funds as compared to less populated and smaller districts. This paper formulates a mathematical model that estimates the amount to be allocated to each district. Then to further prioritise the projects of any department a performance matrix is developed. The matrix ranks the public sector development projects.